Identifikasi Added and Non-Value Added activities Melalui Analisis Just In Time Pada Pekerjaan Pondasi Bore Pile - Simanullang, Joel M (Politeknik Pekerjaan Umum, 2024)
A construction project is a complex job because it involves various resources to achieve the targets of the project. Management of these resources must be carried out with the aim of achieving high productivity. The aim of this research is to determine activities that have added value (Value Added activity) and activities that do not have added value (non-Value Added activity) as well as to evaluate the productivity efficiency of machines and tools in Bore Pile foundation work. The author uses the Just In method Time to identify the effectiveness and efficiency of Bore Pile foundation work. Just In Time will focus on reducing waste so that it can increase productivity. The application of the Just In Time method is only used for resources, namely machines and tools needed for a job. This method will be assisted by the Manufacturing Cycle Effectiveness concept to measure the percentage of Value Added activities. The research results show that there are still several machines or heavy equipment with a percentage of non-Value Added activity that is greater than Value Added activity. This is caused by quite a lot of waiting time and Moving time, resulting in smaller Value Added activity.